Hydroxyapatite/zirconia-microfibre composites with controlled microporosity and fracture properties prepared by electrophoretic deposition. Issue 9 (November 2015) - Drdlik, Daniel; Slama, Martin; Hadraba, Hynek; Cihlar, Jaroslav
Abstract: The stabilisation of hydroxyapatite (HA) particles in dispersions containing 2-propanol and monochloroacetic acid (MCAA) was studied. The surface of HA (Ca 2+ cations) was stabilized by chemical adsorption of non-dissociated MCAA molecules via polar Cl atoms followed by dissociation (cleavage of the protons), which led to negative charging of the HA particles. Colloidal dispersions were milled for 0, 2 and 24 h in a planetary ball mill before electrophoretic deposition (EPD). The electrical conductivity of dispersions was modified by adding an indifferent electrolyte (LiCl) to obtain crack-free deposits with a smooth surface. HA and HA/t-ZrO2 composites containing 2, 4, 8 and 16 wt% zirconia microfibres were prepared by EPD. HA decomposed into α-TCP, β-TCP and partially substituted calcium phosphate by the action of Li + cations during sintering. Elastic modulus and Vickers hardness of composites increased with milling time of the dispersions prior to EPD and decreased with the quantity of zirconia microfibres in the deposits, depending on the composite density. Fracture toughness of the composites was twice as high as that of pure HA due to the presence of orientated zirconia microfibres, finer microstructure, tougher β-TCP phase and pores. The two-week soaking in simulated body fluid revealed the bioactivity of all prepared materials.